Life Cycle Assessment (LCA) and Wind Power Generation: Application of the Methodology and the Generator to Power System - Silva,Mozart Tavares da (2018)
ABSTRACT Sustainability and economics are current issues in the generation of electricity. The energy matrix is diversified and some forms have stood out, such as wind. Some tools have been developed to improve project efficiency, one of which is Life Cycle Assessment (LCA). This presents solidity when assisting projects financially and environmentally, evaluating materials and processes. The present study aimed to analyze the application of LCA in a wind power plant. After searching the main databases and using filters, the analysis was developed from the information of an article that described the application of the LCA to a wind power plant using computational simulation, providing an overview of the production and potential environmental impacts for the process manufacturing, parts maintenance, disposal and recycling at end of lifespan. The phases, steps and the threshold diagram of the LCA system were observed. The results showed a high rate of reuse/recycling of some materials and significant reductions in emissions, financial costs and abatement of environmental payback if the materials were recycled at the end of lifespan. Recycling has shown positive environmental aspects and a significant cost reduction, allowing the expansion of markets and optimization of wind projects.